2011
DOI: 10.1007/s00420-011-0625-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of work-time influence on health and well-being: a quasi-experimental intervention study among eldercare workers

Abstract: The introduction of self-scheduling can successfully increase employee work-time influence. Yet, this study does not support the theory that increased work-time influence leads to better health and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…To the best of Ingre et al our knowledge, such data has not been published before and our data support the hypothesis that relative personal fit is present in self-rostering (9,19). The association between diurnal type and actual working hours suggest that the shift workers to some extent could plan their schedules according to their preferred sleep/wake behavior.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To the best of Ingre et al our knowledge, such data has not been published before and our data support the hypothesis that relative personal fit is present in self-rostering (9,19). The association between diurnal type and actual working hours suggest that the shift workers to some extent could plan their schedules according to their preferred sleep/wake behavior.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies on self-rostering have not been able to show any direct effects on health (19,20), although, one study observed that a majority of the workers (63%) were positive to self-rostering (20), and self rated lack of fit was related to an intention to leave work (18). The reason for lack of effects on health might be related to various confounders associated with shift work such as socioeconomic status, selection mechanisms, and/ or small effects sizes due to limited time of exposure.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…(26,28,29)]. After all: a specific WTC intervention can be theorized to stimulate WTC, but this may not be evident in practice [cf.…”
Section: Study the Intervention Contentmentioning
confidence: 99%
“…The employee's ability to influence working hours (worktime control) has been associated with improved work-life balance (4-6), fewer subjective health complaints (7), less medically certified sickness absence (8), lower likelihood of worker disability pension (9), and reduced turn-over (10). Although other studies failed to find similar effects (11)(12)(13), Joyce et al (14) tentatively concluded in their Cochrane review that flexible working interventions that increase worker control and choice are likely to have a positive effect on health outcomes but also that further intervention studies are needed. Furthermore, evidence is lacking on mechanisms through which increased worktime control may affect social life and health.…”
mentioning
confidence: 99%